Chapter Cognitive Stages in Rational Thinking - toward Human Technology - Laakkonen, Mika (Proceedings e report, 2018)
The main idea behind this research paper is that modern information and communication technology could be better made to serve human beings, if we could specify more precisely the process of human thought and action. The cognitive stages of rational thinking has been studied from the user interface and product point of view but there does not seem to be any generally accepted model for the dynamics involved in cognitive stages in literature. In addition, a few studies have investigated the cognitive stages in rational thinking process from human centric point of view, i.e. how the skills are actually learned.